The Importance of Reference Materials and Method Validation for Advancing Research on the Health Effects of Dietary Supplements and Other Natural Products - Hosbas Coskun, Sanem; Wise, Stephen A.; Kuszak, Adam J. (Frontiers in Nutrition, 2021)
Insufficient assessment of the identity and chemical composition of complex natural products, including botanicals, herbal remedies, and dietary supplements, hinders reproducible research and limits understanding mechanism(s) of action and health outcomes, which in turn impede improvements in clinical practice and advances in public health. This review describes available analytical resources and good methodological practices that support natural product characterization and strengthen the knowledge gained for designing and interpreting safety and efficacy investigations. The practice of validating analytical methods demonstrates that measurements of constituents of interest are reproducible and appropriate for the sample (e.g., plant material, phytochemical extract, biological specimen). In particular, the utilization of matrix-based reference materials enables researchers to assess the accuracy, precision, and sensitivity of analytical measurements of natural product constituents, including dietary ingredients and their metabolites. Select case studies are presented where the careful application of these resources and practices has enhanced experimental rigor and benefited research on dietary supplement health effects.